Statement of assets, liabilities and net worth (SALN) - a subsystem of University of the Philippines Mindanao Human Resources Information System (UPMin HRIS) - Soberano, Hilton Lanuza (2011)
In UP Mindanao, employees are required to submit Statement of assets, liabilities and net worth (SALN) forms annually. The process of filling-up and submitting the forms were manual and time-consuming. In line with the development of the Human Resources Information System (HRIS) of the said institution, this study developed a subsystem to address the specific processes which concerns the SALN. This enabled employees to fill-up their respective SALN online and generate reports that summarize their assets, liabilities and net worth per year. Also, they are able to protect their individual information using password-protected accounts. Through the system, human resources personnel are able to generate annual administrative summary reports, hence freeing them from routine tasks to focus on more strategic functions, making them more productive. The subsystem also caters to specific functions necessary for the locality e.g. joint accounts.